The Hsf world: classification and properties of plant heat stress transcription factors - Nover, Lutz (Cell Stress Society International, 1996)
Based on the partial or complete sequences of 14 plant heat stress transcription factors (Hsfs) from tomato, soybean, Arabidopsis and maize we propose a general nomenclature with two basic classes, i.e. classes A and B each containing two or more types of Hsfs (HsfA1, HsfA2 etc.). Despite some plant-specific peculiarities, essential functional domains and modules of these proteins are conserved among plants, yeast, Drosophila and vertebrates. A revised terminology of these parts follows recommendations agreed upon among the authors and representatives from other laboratories working in this field (see legend to Fig.1). Similar to the situation with the small heat shock proteins (sHsps), the complexity of the hsf gene family in plants appears to be higher than in other eukaryotic organisms.